Effects and mechanisms of acupuncture analgesia mediated by afferent nerves in acupoint microenvironments - Fan, Zezhi; Dou, Baomin; Wang, Jiangshan; Wu, Yongjian; Du, Simin; Li, Jiashan; Yao, Kaifang; Li, Yanwei; Wang, Shenjun; Gong, Yinan; Guo, Yi; Xu, Zhifang (Frontiers in Neuroscience, 2024)
In the past few decades, the use of acupuncture analgesia in clinical practice has increased worldwide. This is due to its various benefits, including natural alleviation of pain without causing various adverse effects associated with non-steroidal anti-inflammatory drugs (NSAID) and opioids. The acupoint represents the initial site of acupuncture stimulation, where diverse types of nerve fibers located at the acupoint hold significant roles in the generation and transmission of acupuncture-related information. In this study, we analyzed the patterns and mechanisms of acupuncture analgesic mediated by acupoint afferent fibers, and found that acupuncture stimulates acupoints which rapidly and directly induces activation of high-density primary afferent fibers under the acupoints, including myelinated A fibers and unmyelinated C fibers. During acupuncture stimulation at the muscle layer, the analgesic effects can be induced by stimulation of A fiber threshold intensity. At the skin layer, the analgesic effects can only be produced by stimulation of C fiber threshold intensity. Electroacupuncture (EA) activates A fibers, while manual acupuncture (MA) activates both A and C fibers. Furthermore, acupuncture alters acupoint microenvironments, which positively modulates afferent fibers, enhancing the transmission of analgesic signals. In addition to local activation and conduction at acupoints, nerve fibers mediate the transmission of acupuncture information to pain centers. In the spinal cord, acupuncture activates neurons by inducing afferent fiber depolarization, modulating pain gating, inhibiting long-term potentiation (LTP) of the spinal dorsal horn and wide dynamic range (WDR) neuronal activities. At higher nerve centers, acupuncture inhibits neuronal activation in pain-related brain regions. In summary, acupuncture inhibits pain signal transmission at peripheral and central systems by activating different patterns of afferent fibers located on various layers of acupoints. This study provides ideas for enhancing the precise application and clinical translation of acupuncture.